Komunikasi Organisasi: Dimensi-Dimensi Yang Dapat Meningkatkan Kinerja (Studi Kasus di CV Citra Gemilang Banjarmasin) - Nadila Deryza Syofrin; Mariyam; Marhusin (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: This study aims to investigate the dimensions of communication in the context of complex groups or organizations, with an emphasis on the role of communication in improving the performance of CV Citra Gemilang. Qualitative research is used in case studies as a framework. Primary data is obtained through observation and interviews with related parties, namely: Director, Operational Manager, Operational Staff, Admin Staff, and Finance Staff, which are then followed by data analysis including the stages of data reduction, data presentation, and drawing conclusions. This study examines in depth the vertical communication downwards and upwards, as well as horizontal communication that occurs in the CV Citra Gemilang environment. The results of the study show that in the study at CV Citra Gemilang, vertical and horizontal communication play a vital role. Vertical communication includes the distribution of information from upper management to the operational level and vice versa, ensuring the flow of information appropriately and efficiently through face-to-face meetings, WhatsApp, and email. Active efforts are made to overcome obstacles such as late reports by reprimanding and encouraging employee responsiveness. Vertical communication also emphasizes the ethics of formal communication with superiors. On the other hand, horizontal communication involves sharing information and collaboration between teams, especially in accounting. Challenges such as scheduling meetings and misunderstandings of messages are overcome through the use of electronic communication and open communication. Overall, vertical and horizontal communication at CV Citra Gemilang creates an inclusive, collaborative, and productive work environment